Bergey's Manual of determinative bacteriology (Williams & Wilkins Co., 1994)
The aim of this manual is to provide the user with the best means of identifying bacteria. It is based mainly on the four-volume "Bergey's Manual of Systematic Bacteriology". Many species or genera have been reclassified, resulting in new names or combinations. Where there is disagreement with some proposed classification, a brief mention of it is provided for the sake of synonymy. The book aims to allow the reader to identify an unknown organism to the level of genus and, if possible or practical, to the level of species.